Cultural Identity at Risk: The Magar Language and Its Endangerment - Magar, Anita; Lamichhane, Hari Krishna (Journal of Development Review, 2025)
This research critically examines the factors behind the endangerment of indigenous languages in Nepal in general and the decline of Magar language in Malbase Village from Ilam district in Eastern Nepal in particular. According to the Census report (2021), the Magars constitute one of the largest indigenous community in the country; however, they are facing the major challenge of the endangerment and decline of their native and mother language being influenced by Nepali language and other societal influences. Based on field survey and interviews to the people from the study area along with data analysis and interpretation of their opinions, this research examines the role of preference to mainstream language, migration, mixed communities, and inter-caste marriage as key contributors to language decline. This research is significant since language endangerment is a burning problem worldwide. It addresses the research gap in the area of indigenous language loss in general and Magar language in particular. The research points out the role of community, government, institutions and organizations and their efforts in revitalizing indigenous languages like Magar language in preserving the cultural identity and heritage of the communities.